Komunikasi Dakwah Pada Masyarakat Adat Kampung Dukuh Garut - Dede Sihabudin (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2019)
The Dukuh traditional village community is a strong community with the principle of holding ancestral traditions based on Islamic values. The purpose of this study was to describe the experiences, understandings, and meanings of the da'is in Dukuh village and to describe the effectiveness of his da'wah communication. The research method used is the phenomenology method with Harold Lasswell's communication theory which assumes 5 elements of communication. The results of this study indicate that da'i cannot impose heavy material because the majority of the livelihoods of the residents are farmers; each da'i understands that preaching must be carried out by everyone in the village of Hamlet with their respective abilities; the meaning of da'wah according to the preachers in the village of Hamlet is 5T, namely the purpose of inhaling (khaufullāh and rahmatullāh), the task of inhaling (worship), the procedure of hrup (by being obedient to Allāh, apostles and government), inhaled challenges (must be strong against trials) , and Tuntung breathes (always expresses himself to face death by worship). Da'wah in the Dukuh Customary village environment has run quite effectively because the community generally adheres to the 5T principle which has been maintained for generations. AbstrakMasyarakat kampung adat Dukuh merupakan masyarakat yang teguh berprinsip memegang tradisi leluhur berasas nilai-nilai Islam. Tujuan penelitian ini adalah untuk mendeskripsikan pengalaman,  pemahaman, dan pemaknaan para da’i yang ada di kampung Dukuh serta menggambarkan keefektifan komunikasi dakwahnya. Metode penelitian yang diguanakn adalah metode fenomenologi dengan teori komunikasi Harold Lasswell yang mengasumsikan 5 unsur komunikasi. Hasil penelitian ini menunjukan bahwa da’i tidak bisa memaksakan materi yang berat karena mayoritas mata pencaharian penduduknya adalah petani; setiap da’i memahami bahwa dakwah wajib dilakukan setiap orang di kampung Dukuh dengan kemampuannya masing-masing; makna dakwah menurut para da’i di kampung Dukuh adalah 5T, yaitu Tujuan hirup(khaufullāh dan rahmatullāh), Tugas hirup (ibadah), Tata cara hrup (dengan taat kepada Allāh, rasul dan pemerintah), Tantangan hirup (harus kuat menghadapi cobaan), dan Tuntung hirup (selalu memperispkan diri untuk menghadapi kematian dengan ibadah). Dakwah di lingkungan kampung Adat Dukuh telah berjalan cukup efektif karena masyarakatnya secara umum memegang teguh prinsip 5T yang telah dijaga secara turun-temurun.